Protocol-directed insulin infusion sliding scales improve perioperative hyperglycaemia in critical care - Hui, Man Lin; Kumar, Arun; Adama, Gary G. (BioMed Central, 2012)
Perioperative hyperglycaemia is associated with poor outcomes in patients undergoing cardiac surgery. Frequent postoperative hyperglycaemia in cardiac surgery patients has led to the initiation of an insulin infusion sliding scale for quality improvement.